2021
DOI: 10.21608/mid.2021.78200.1162
|View full text |Cite
|
Sign up to set email alerts
|

Detection of plasmid-mediated colistin resistance in carbapenem-resistant Escherichia coli and Klebsiella pneumoniae isolates in Suez Canal University Hospitals

Abstract: Background:The polymyxins including colistin are the "last resort" antibiotics for treatment of infections with carbapenem resistant Enterobacteriaceae. Recently, transferable colistin resistance mediated by the mcr-genes has been described in Enterobacteriaceae. The testing of colistin susceptibility is challenging. The aim of the work is to detect the occurence of mcr-1 and mcr-2 genes in phenotypically colistin-resistant carbapenem resistant Escherichia coli (E. coli) and Klebsiella pneumoniae (K. pneumonia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 12 publications
2
6
0
Order By: Relevance
“…Klebsiella spp were the most frequent CRGNB isolates (36.1%) followed by Escherichia coli (32.9%), Pseudomonas aeruginosa (12.9%), Acinetobacter spp (8.4%), Enterobacter spp (5.8%) and Citrobacter spp (3.9%). Matching with carbapenem resistance rates (54.5% and 55.8%) in previous studies 17,4 . On the contrary, lower rates (18.5% and 23.1%) were reported in other studies 18-19 .…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Klebsiella spp were the most frequent CRGNB isolates (36.1%) followed by Escherichia coli (32.9%), Pseudomonas aeruginosa (12.9%), Acinetobacter spp (8.4%), Enterobacter spp (5.8%) and Citrobacter spp (3.9%). Matching with carbapenem resistance rates (54.5% and 55.8%) in previous studies 17,4 . On the contrary, lower rates (18.5% and 23.1%) were reported in other studies 18-19 .…”
Section: Discussionsupporting
confidence: 60%
“…Carbapenem resistant Enterobacteriaceae (CRE) comprise both carbapenemase producing (CP-CRE) which produce carbapenemase enzymes hydrolyzing carbapenem and non-carbapenemase producing CRE (non-CP-CRE) strains that have other causes like drug efflux pumps and outer membrane protein structural mutations resulting in drug impermeability 4,23 . In this research, 129 of CRGNB isolates (83.2%) were carbapenemase positive by mCIM, among them 85 isolates (65.9%) were metallo-β lactamase producers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of them, 35 were discovered to be colistin resistant. Multiplex PCR revealed that some mcr-genes (mcr-1, mcr-2, and mcr-3 genes) were found in 44% (21) isolates, 95% (20) E. coli, and 5% (1) K. pneumoniae. mcr-1 (85%), mcr-1 and mcr-2 combined (5%), mcr-2 alone (5%), and mcr-2 alone and mcr-3 combined (5%).…”
Section: Discussionmentioning
confidence: 99%
“…The amplification was seen by gel-electrophoresis on 1.5% agarose gel (at 130 Volts), followed by ethidiumbromide staining. 21,22…”
Section: Dna Extraction and Pcr Amplificationmentioning
confidence: 99%